Burden of disease and economic impact of human Streptococcus suis infection in Viet Nam - Huong, VTL; Turner, H; Kinh, NV; Thai, PQ; Hoa, NG; Horby, P; Van Doorn, HR; Heiman, W (Oxford University Press, 2019)
Background Streptococcus suis is a zoonotic disease mainly affecting men of working age and can result in death or long-term sequelae, including severe hearing loss and vestibular dysfunction. We aimed to quantify the burden of disease and economic impact of this infection in Viet Nam. Methods The annual disease incidence for the period 2011–2014 was estimated based on surveillance data using a multiple imputation approach. We calculated disease burden in disability-adjusted life years (DALYs) and economic costs using an incidence-based approach from a patient’s perspective and including direct and indirect impacts of S. suis infection and its long-term sequelae. Results The estimated annual incidence rate was 0.318, 0.324, 0.255 and 0.249 cases per 100 000 population in 2011, 2012, 2013 and 2014, respectively. The corresponding DALYs lost were 1832, 1866, 1467 and 1437. The mean direct cost per episode was US$1635 (95% confidence interval 1352–1923). The annual direct cost was US$370 000–500 000 and the indirect cost was US$2.27–2.88 million in this time period. Conclusion This study showed a large disease burden and high economic impact of S. suis infection and provides important data for disease monitoring and control.